Downregulation of Connexin 43 promotes vascular cell loss and excess permeability associated with the development of vascular lesions in the diabetic retina - Tien, Thomas (Molecular Vision, 2014)
PURPOSE: To determine whether downregulation of Connexin 43 (Cx43) expression promotes development of acellular capillaries (ACs), pericyte loss (PL), excess permeability, and retinal thickening in rat retinas. METHODS: Control rats, diabetic rats, and rats intravitreally injected with Cx43 siRNA or scrambled siRNA were used in this study to determine if acute downregulation of Cx43 expression contributes to retinal vascular cell death and excess permeability. Western blot (WB) analysis and Cx43 immunostaining were performed to assess Cx43 protein levels and distribution in the retinal vessels. Concurrently, retinal networks were subjected to terminal deoxynucleotidyl transferase-mediated uridine 5′-triphosphate-biotin nick end labeling (TUNEL) assay and counter-stained to assess the number of apoptotic cells, ACs, and PL. Assessment of fluorescein isothiocyanate-dextran (FITC-dex) extravasation from retinal capillaries and optical coherence tomography (OCT) were performed to determine retinal vascular permeability and retinal thickness, respectively. RESULTS: WB analysis indicated a significant decrease in the Cx43 protein level in the retinas of the diabetic rats and those intravitreally injected with Cx43 siRNA compared to the retinas of the control rats. Likewise, the retinal vascular cells of the diabetic rats and the Cx43 siRNA-treated rats showed a significant decrease in Cx43 immunostaining. Importantly, the number of apoptotic cells, ACs and PL, FITC-dex extravasation, and thickness increased in the retinas of the diabetic and Cx43 siRNA-treated rats compared to those of the control rats. CONCLUSIONS: Results indicate that downregulation of Cx43 expression alone induces vascular cell death and promotes vascular permeability in the retina. These findings suggest that diabetes-induced downregulation of Cx43 participates in promoting retinal vascular lesions associated with diabetic retinopathy (DR).